Pengontrolan Jarak Jauh Motor DC Dengan AntarMuka Sebuah Web Sebagai Penggerak Pintu Gerbang - SANTO FERNANDO; IRSAN TAUFIK ALI; ANTONIUS RAJAGUGUK (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Electric motors are much in use as a driver, especially the motor current (DC). One pengotrolan motors direct current (DC) is controlling the direction of rotation. in this case the direction of rotation of the electric motor control (DC) can be applied as the driving gate in everyday life, so as to open and close the gate can be done remotely with a web interface. With the use of computer technology is remote controlling a DC motor with a web interface as the driving gate. controlling the direction of motor rotation direction will be shaking the gate is open or closed. To be able dimamfaat output signal from the computer port required a series of small signal driver that can be used to drive the object to be controlled remotely so that it can mengerakan perputran motors. When relay 1 works then brush motor will get a positive voltage source positive and negative brush motor is connected to the negative pole of the voltage source. Thus, the motor will work the gate open. In the same way to move the contact relay 2, then the opposite conditions occur that the motor will rotate the opposite direction of rotation, so that the gate is closed.  Keywords: direct current motor, control, relay computer port.